1967
DOI: 10.1161/01.res.21.4.507
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Node Impulses and Atrial Fibrillation

Abstract: In atrial muscle strips from rabbits, fibrillation occurred in a solution low in potassium, with or without a high calcium content, and the role of the sinus node in inducing atrial fibrillation was examined by microelectrodes and by direct close bipolar lead electrocardiograms. In right atrial strips that included the sinus node, the sinus node action potential often just preceded spontaneous fibrillation or premature beats. In left atrial strips in a similar condition, the incidence of spontaneous fibrillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

1969
1969
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 6 publications
(3 reference statements)
1
4
0
1
Order By: Relevance
“…Our results provide support for this view since the maximum response rate (present results) is in the range of firing (8-20 Hz) observed during atrial fibrillation (Sano et al, 1967;Kositsky et al, 1972a). Disturbances of intercellular electrical coupling during fibrillation contribute to disturbances of circular pathways of propagation and elimination of reentry.…”
Section: Discussionsupporting
confidence: 85%
“…Our results provide support for this view since the maximum response rate (present results) is in the range of firing (8-20 Hz) observed during atrial fibrillation (Sano et al, 1967;Kositsky et al, 1972a). Disturbances of intercellular electrical coupling during fibrillation contribute to disturbances of circular pathways of propagation and elimination of reentry.…”
Section: Discussionsupporting
confidence: 85%
“…It is therefore possible that in cattle AF is a cause of histopathological changes in the SA node. Intriguingly, it has been reported that, in experiments on dog hearts, AF was easily produced by some drugs when the SA node was intact, but was difficult to produce when the SA node was injured [30].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that it is easier to produce either atrial or ventricular fibrillation in large than small hearts and that therapeutic termination of either form of fibrillation is more difficult in large hearts. Both experimental and clinical evidence furthermore indicates that presence or absence of continued activity by the sinus node influences whether or not atrial fibrillation will occur (Sano et al, 1967;Azuma et al, 1972;Kirchhof, 1989;Page, 1992), and default of the sinus node may help fibrillation to begin andlor be perpetuated. A sinus node as large and well organized as that of the sperm whale may be more difficult to unstabilize or suppress.…”
Section: Discussionmentioning
confidence: 99%